Valsartan effects on platelet activity in patients with arterial hypertension and metabolic syndrom - I. N. Medvedev; T. A. Kumova (Российский кардиологический журнал)
То assess angiotensin II receptor blocker effects on platelet aggregation in arterial hypertension (AH) and metabolic syndrome (MS), 34 patients were administered valsartanfor 16 weeks. The dynamics of anthropometry parameters, blood lipids, plasma and platelet lipid peroxidation, blood and blood cell antioxidant potential, as well as platelet aggregation was investigated. Statistical analysis included Student and systemic multi-factor analysis methods. In AH and MS patients, valsartan improved peroxidation syndrome and platelet aggregation. For weight reduction, valsartan should be combined with non-pharmaceutical methods.